Climate Change & Food Security Vulnerability Assessment. Toolkit for assessing community-level potential for adaptation to climate change - Bioversity International; Ulrichs, Martina; Cannon, Terry; Institute of Development Studies; Newsham, Andrew; Naess, Lars Otto; Marshall, Mipsie (2015)
This CCAFS Working Paper presents a participatory methodology that has been designed to provide organizations with the tools to understand the interrelations between climate impacts, food systems and livelihood strategies at the local level, while taking into consideration traditional /indigenous knowledge of the participating community. The toolkit developed applies a multidimensional view of the vulnerability of livelihood strategies to climate change, with a focus on differentiated access and entitlements to livelihood resources and food for different groups within a locality or community (often determined according to gender, ethnicity and socioeconomic class). It includes step by step instructions on how to implement participatory tools that were adapted to answer the following questions: Why are people vulnerable? How are they vulnerable to climate change? What consequences does this have for their food security? Implementing this methodology will provide an initial understanding of the local context and vulnerability profiles, which, combined and triangulated with other sources of information (meteorological data, socio-economic indicators etc.), feeds into the process of identifying adaptation measures.